The Trade Unions and Contemporary Protest. Solidarity and Symbolic Protest, Lessons for Labour from the Québec City Summit of the America - MacKay, Kevin (Labour/Le Travailleur, 2002)
Abstract This photo-essay explores the significance of April 2001’s Summit of the Americas for labour and other groups within the counter-globalization movement. Through text and images, the first section presents the Summit demonstrations as an instance of creative and symbolic protest, in which participants and observers were educated, empowered, and radicalized. It is argued that direct action protest, through the creation of immediate affective bonds and collective identities, can be a powerful force for generating solidarity between diverse movement groups. The second section examines the role of labour in Québec City, and in related counter-globalization protests. The tension between conservatism and radicalism within the trade union movement and between workers and other movement groups is explored, and it is argued that direct action protest provides means through which these tensions can be productively resolved. The final section asks what lessons Québec City can teach labour and other movement groups, and what role mass protest might play in achieving the goals of counter-globalization.